Strategi Pengelolaan Sampah dalam Mendukung Program Zero Waste di Desa Pulau Maringkik - Krisna Aditya Warman; Budiman Budiman; Ersa Safira; I Gede Krisna Dharma Arta; Siska Rosalinda; Putri Diana; Didik Rijal Lajuardi; Amira Fatinah; Dandy Hidayat; Dea Marlina; Muhammad Akmal Malazy; Muhammad Dira Fathony; Rosanti Wahidatussolihah; Herpan Syafii Harahap (Universitas Mataram, 2022)
Maringkik Village is a fishing village located in East Lombok. This village has promising tourism potential due to the condition of the island which is surrounded by beaches with beautiful landscape. The natural beauty of Maringkik Village is starting to be covered by a serious waste problem, one of the waste problems is the unavailability of proper garbage dump, so people throw garbage into the sea or on the coast which results in environmental pollution. Therefore, an effort is needed to overcome this problem. There are several efforts that are expected to decrease the waste problem in Maringkik Village, among others, implementing a waste audit, socializing waste management and waste banks, establishing a waste bank and processing plastic waste into Eco brick that can be created into useful goods.